Differences in time and space use between two sympatric Acrocephalus warblers with similar diets. Issue 2 (2nd April 2016) - Ceresa, Francesco; Belda, Eduardo J.; Gómez, Jaime; Miñana, Ignacio J.; Soler, Lydia; Villarroya, Julia; Monrós, Juan S.
ABSTRACT: Capsule: We found high diet overlap and different uses of space and time between Moustached Warblers Acrocephalus melanopogon and Reed Warblers Acrocephalus scirpaceus breeding in sympatry at a marshland in Spain. Aims: To study the degree of diet overlap between both species, their space use on a local scale and their breeding phenologies. Methods: We studied the breeding phenologies of the two species by standardized ringing activity. Spatial distribution was investigated by point counts. We determined diet composition from emetic samples and we collected invertebrates by standardized sweep-netting to estimate food availability. Results: Diet and prey selection were similar among species. Conversely, spatial overlap was relatively small (<50%) and breeding phenologies were not synchronized. Both food availability and the overall abundance of the two species increased throughout the breeding season. Conclusion: The two species are potential competitors for food and the observed differences in spatial and temporal niches may represent a way to lower competition for trophic resources: Moustached Warblers could reduce competition by breeding early, while Reed Warblers could avoid settling in areas occupied by the other species.